The ANFIS Model Approach in Classifying the Characteristics of Children with Special Needs at SLB in Southwest Papua - Ermin; La Jupriadi Fakhri; Fisal Aliama (Jurnal Penelitian Pendidikan IPA, 2025)
Special Elementary Education (SDLB) has a strategic role in providing equal access to education for Children with Special Needs (ABK). Observations at one of the Special Needs schools (SLB) in Southwest Papua show that the initial assessment process of ABK characteristics based on age, IQ, and motor skills has not been effective. This study aims to develop a system based on the Adaptive Neuro-Fuzzy Inference System (ANFIS) model to assist the initial classification process of ABK characteristics and support initial assessments at school. The ANFIS model is used to study the nonlinear relationship between input variables and classification results. Testing is carried out using validated data to assess the level of accuracy and consistency of the model. The results show that the ANFIS model-based system has an accuracy level of 85.7% with stable predictive capabilities on most of the test data. These findings show that the integration of ANFIS into a web-based system can be an effective tool for teachers in conducting initial assessments, so that the process of identifying ABK characteristics can be carried out more quickly, objectively, and efficiently.